Study of Knowledge, Attitude and Practice among the Nursing Students Regarding COVID-19 Preparedness in A Rural Tertiary Care Center in Eastern India - Uttam Majumder; Jagadish Biswas; Avik Kumar Layek; Sabita Tamang (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present pregression of the highly contagious novel coronavirus [COVID-19] has been testing thehealthcare system globally pressing the medical staff everywhere. Present and future healthcare workers’updated knowledge, proper attitude towards the pandemic and adequate preventive practices are ofparamount importance for the combat effectiveness of the healthcare burden.This study assessed theknowledge, practice and attitudes regarding COVID-19 among the nursing students of a tertiary care centerin Eastern India. KAP scores were compared with their socio-demographic variables. Inter-relation betweenknowledge, attitude and practice was also assessed.Out of the 131 students participated in the study the KAPparameters were not significantly different based on the socio-demographic factors. Though knowledgeand attitude parameters were positively correlated among them, it was found that practice was negativelycorrelated to both knowledge and attitude. This finding can be attributed to them being non-exposed andinexperienced in the regular healthcare activities as well to the fact that Indian population was to some extentunprepared to cope up with this type of epidemic for a long time. Training on the updated knowledge alongwith exposure to simulated environment with scheduled supervision to reflect the behavior of the studentsis of great importance so that in extreme situation, the trainee students can also come handy into utilizationif needed.